General Integral Operator of Analytic Functions Involving Functions with Positive Real Part - B. A. Frasin (Journal of Mathematics)
Let be the integral operator defined by where each of the functions and are, respectively, analytic functions and functions with positive real part defined in the open unit disk for all . The object of this paper is to obtain several univalence conditions for this integral operator. Our main results contain some interesting corollaries as special cases.